2022
DOI: 10.1109/access.2022.3204696
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-Layer Transferable Adversarial Attack With DNN Attention

Abstract: The widespread deployment of deep learning models in practice necessitates an assessment of their vulnerability, particularly in security-sensitive areas. As a result, transfer-based adversarial attacks have elicited increasing interest in assessing the security of deep learning models. However, adversarial samples usually exhibit poor transferability over different models because of overfitting of the particular architecture and feature representation of a source model. To address this problem, the Intermedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In general, the material, stress, velocity, temperature, and other factors affect the friction coefficient between a tool and a chip [4], but researchers in the field of tribology have been attempting to describe in detail how the friction interface process and the deformation mechanism of materials work. It is finally confirmed that in solid-solid contact, the friction interface will cause significant material changes, resulting in a third body [7,8], which is also called a friction film, a friction layer [9], a transfer layer [10], a mechanical mixing layer [11], etc. The coolant cannot successfully build a water film under centrifugal and hightemperature conditions to form a solid-solid contact for high-speed internal cooling milling [12].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the material, stress, velocity, temperature, and other factors affect the friction coefficient between a tool and a chip [4], but researchers in the field of tribology have been attempting to describe in detail how the friction interface process and the deformation mechanism of materials work. It is finally confirmed that in solid-solid contact, the friction interface will cause significant material changes, resulting in a third body [7,8], which is also called a friction film, a friction layer [9], a transfer layer [10], a mechanical mixing layer [11], etc. The coolant cannot successfully build a water film under centrifugal and hightemperature conditions to form a solid-solid contact for high-speed internal cooling milling [12].…”
Section: Introductionmentioning
confidence: 99%